PEMASARAN MELALUI APLIKASI ETSY PADA UMKM HANDYCRAFT - Rika Rahayu; Mar'atus Zahro; Dewi Maryam (Universitas Majalengka, 2022)
The COVID-19 pandemic has been running for almost 2 years, so it is a demand for all elements of society to be able to survive in the midst of the current pandemic. Many service and goods business sectors have been affected. Selling goods through the etsy application is relatively easy when compared to other applications selling products with export potential. However, sellers need very interesting work and routines related to documentation and providing customer service for the products to be sold. Problems that occur with MSMEs in Indonesia include the decline in the creativity of handicraft MSMEs during the Covid-19 pandemic, lack of knowledge regarding online marketing platforms, and lack of knowledge regarding export potential. Based on these problems, this service activity is to provide assistance and training with interview and FGD methods through Google meet by explaining the introduction of the ETSY application and designing goods that have a selling value. The implementation method uses three stages, namely problem identification, training and assistance, monitoring and evaluation. Based on community service activities carried out in Bubutan District, which were attended by MSME actors in the District, it can be concluded that several MSME actors in Bubutan District began to include hand-made goods to be marketed through the ETSY application, as well as several MSME actors in Bubutan District. The Bubutan sub-district has income from more than one type of business for entrepreneurship during the pandemic.